Approach by modeling to generate an e-commerce web code from laravel model - M'hamed Rahmouni; Mouad Bouzaidi; Samir Mbarki (Institute of Advanced Engineering and Science, 2023)
The world of web is constantly evolving. Today, we no longer speak of a website but of a web application. The growing difficulty of designing web applications has given rise to solutions and tools. The framework is one of them. Providing a serious framework for development by offering strict development rules, as well as generic and out-of-the-box components, PHP laravel framework is one of them. This paper aims to present the different stages of modeling and development of an enterprise resource planning (ERP) system that will be implemented by PHP laravel by defining the main concepts involved in this information system modeling and development process. To lead and implement the end-to-end development of the said system, we apply the model-driven architecture (MDA) approach. This approach is based on atlas transformation language (ATL). The result of this paper is an Ecore file, a reliable MVC2 web model of e-commerce ERP, which will be the input file to generate the aforementioned system code. To validate this approach, we implemented a case study. The result of this work is very satisfying. Thus, we arrived to generate all necessary elements for this ERP code generation by respecting the MVC2 model and the PHP coding.